Diffuse Attenuation of Clear Water Tropical Reservoir: A Remote Sensing Semi-Analytical Approach - Victor Pedroso Curtarelli; Cláudio Clemente Faria Barbosa; Daniel Andrade Maciel; Rogério Flores Júnior; Felipe Menino Carlos; Evlyn Márcia Leão de Moraes Novo; Marcelo Pedroso Curtarelli; Edson Filisbino Freire da Silva (Remote Sensing, 2020)
The diffuse attenuation coefficient of downwelling irradiance (<semantics>Kd</semantics>) is an essential parameter for inland waters research by remotely sensing the water transparency. Lately, <semantics>Kd</semantics> semi-analytical algorithms substituted the empirical algorithms widely employed. The purpose of this research was to reparametrize a semi-analytical algorithm to estimate <semantics>Kd</semantics> and then apply it to a Sentinel-2 MSI time-series (2017–2019) for the Três Marias reservoir, Brazil. The results for the <semantics>Kd</semantics> semi-analytical reparametrization achieved good accuracies, reaching mean absolute percentage errors (MAPE) for bands B2, B3 and B4 (492, 560 and 665 nm), lower than 21% when derived from in-situ remote sensing reflectance (<semantics>Rrs</semantics>), while for MSI Data, a derived MAPE of 12% and 38% for B2 and B3, respectively. After the application of the algorithm to Sentinel-2 images time-series, seasonal patterns were observed in the results, showing high <semantics>Kd</semantics> values at 492 nm during the rainy periods, mainly in the tributary mouths, possibly due to an increase in the surface runoff and inflows and outflow rates in the reservoir watershed.